Complete mitochondrial genomes of the smooth tail nine-spined sticklebacks Pungitius laevis (Gasterosteiformes, Gasterosteidae). Issue 1 (1st January 2016) - Guo, Baocheng; Shikano, Takahito; Wang, Cui; Merilä, Juha
Abstract: The complete mitochondrial genome sequences of three divergent lineages of the smooth tail nine-spined stickleback ( Pungitius laevis ) were obtained with massive parallel sequencing of their genomic DNA. The genome sequences were 16 574–16 580 bp long, and the gene order and contents were identical to those of other sequenced Pungitius mitogenomes. Although the mitogenome sequences of all three P. laevis lineages clustered within the genus Pungitius, they were clearly distinct and showed divergence comparable to that seen between some Pungitius species.